Investigations on structural, electrical, and third order nonlinear optical properties of benzimidazolium maleate single crystal. (2021) - Sakthy Priya, S.; Balakrishnan, K.; Surendran, P.; Lakshmanan, A.; Pushpalatha, S.; Ramalingam, G.; Rameshkumar, P.; Kaviyarasu, K.; Ashok Hegde, Tejaswi; Vinitha, G.
Abstract: An efficient organic single crystal of Benzimidazolium maleate (BIMA) has been grown by slow solvent evaporation method. The lattice parameters and crystallinity of the crystal was determined by powder X-ray diffraction analysis (PXRD) and the material has compressive strain. In order to various chemical bond and vibrations present in BIMA crystal was confirmed by FTIR spectrum analysis. However, the dielectric constant and dielectric loss of the grown crystal as a function of frequency was measured. In addition solid state parameters like plasma energy, Penn gap and Fermi energy were evaluated for the BIMA single crystal using the empirical relation. Z-scan technique was used to determine the nonlinear refractive index (7.8206 × 10 −10 cm 2 /W), nonlinear absorption coefficient (3.2398 × 10 −05 cm 2 /W) and third order nonlinear susceptibility (5.5378 × 10 −07 esu). It confirms the negative nonlinearity which is applicable in night vision devices.